EU CSDDD POSTPONEMENT: IMPLICATIONS FOR SOUTHEAST ASIAN WORKERS’ HUMAN SECURITY - Surya Tjandra; Celine Reyna Wuisan (Jurnal Paradigma Hukum Pembangunan, 2026)
The EU Corporate Sustainability Due Diligence Directive (CSDDD) was first adopted in 2024. By imposing legal obligations on companies operating in the EU market, the CSDD aims to improve working conditions and safeguard human security beyond the EU borders, particularly in high-risk supply chains such as those in Southeast Asia. While the primary responsibility for human rights and security are with the respective Southeast Asian governments, many of these countries face enforcement challenges that limit effective protections for workers. The CSDDD’s extraterritorial scope complements state obligations by legally requiring multinational corporations to undertake due diligence on their global supply chains. However, its recent postponement to 2027-2029 raises concerns about regulatory gaps and enforcement challenges. This paper analyzes the impact of the CSDDD delay on human security in Southeast Asian supply chains, including how it impacts the leverage of local workers, trade unions, and NGOs in holding multinational corporations accountable. This paper uses a comparative and descriptive legal analysis of the CSDDD’s drafts and amendments, case studies from Indonesia and Vietnam, and stakeholder perspectives from NGO reports and trade union statements. The regulatory postponement poses a threat to human security in critical Southeast Asian industries. In conclusion, the delay in the CSDDD’s implementation risks stalling critical progress towards a sustainable and ethical global supply chain. To address this regulatory gap, interim solutions including bilateral cooperation, enforceable contractual protections, and stakeholder engagement mechanisms are needed to protect vulnerable workers and enforce corporate accountability.